Womens Strength and Ability: American Feminist Ideals in Soul Surfer (2011) Movie - Salwa Ine Kautsar; Arido Laksono (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This research examines the representation of womens strength and American feminist ideals in the movie Soul Surfer (2011). The main focus of this research is Bethany Hamiltons struggles in embodying feminist values. The theories that were used in this research are based on feminist theories form Tong and Butler. The method used in this research is literature review. The results of the research indicate that, out of 10 samples, Bethany is depicted as going against societys expectations by return to the world of surfing after enduring a life-changing incident. Bethany embodies the values of womens empowerment and gender equality. This finding provides insights into how Soul Surfer promotes feminist values by celebrating womens strength, agency, and resilient spirit in the face of obstacles, thereby encouraging a more profound awareness of gender equality and womens empowerment in the modern society